PENGEMBANGAN E-MODUL PEMBELAJARAN IPAS BERBASIS PENDEKATAN DEEP LEARNING UNTUK SISWA KELAS V SD - Rohmatus Syafi’ah; Rahyu Setiani (LPPM Universitas Cipta Mandiri, 2026)
This study aims to develop an innovative e-module for Natural and Social Sciences (IPAS) learning in Grade V elementary school based on the Deep Learning approach, addressing the limited availability of interactive and pedagogically grounded digital teaching materials that foster meaningful and reflective learning. Using a Research and Development (R&D) design with a modified ADDIE model, the study focused on the analysis, design, and development stages, followed by limited implementation and evaluation. The product was validated by three experts in subject matter, media, and language, and its readability was tested by 25 elementary school students. Data were collected using expert validation questionnaires and student readability questionnaires, then analyzed quantitatively through descriptive statistics. The results showed that the e-module was highly valid with scores of 90.97% for subject matter, 87.12% for media, and 88.89% for language, while the readability test reached 93.15% in the “very good” category. These findings confirm that the e-module is accurate, well-organized, visually engaging, linguistically appropriate, and effective in supporting independent learning, as well as integrating interactive elements such as videos, quizzes, and exploratory tasks to enhance deep learning. However, the study was limited to small-scale implementation in one school, so the generalizability of the results is constrained. Future research is suggested to test the effectiveness of the e-module in broader contexts and explore adaptive technology integration such as artificial intelligence and learning analytics to improve personalization and sustainability of digital learning innovations.